Assessing the effectiveness of targeted educational interventions on enhancing self-efficacy and foot care practices among diabetic women in Jordan - Heba Hijazi; Heba Hijazi; Rabah Al Abdi; Rabah Al Abdi; Sawsan Abuhammad; Sawsan Abuhammad; Wegdan Bani Issa; Alham Al-Sharman; Alham Al-Sharman; Nesreen Saadeh; Alounoud AlMarzooqi; Fatma Refaat Ahmed; et al. (Frontiers in Public Health)
BackgroundDiabetic foot is a major public health issue, leading to increased morbidity and mortality among diabetic patients. This study aimed to evaluate the effectiveness of targeted health education interventions on self-efficacy and foot care practices among diabetic women in Jordan.MethodsA pretest-posttest, quasi-experimental design was used to collect data from 76 diabetic women at a tertiary hospital in northern Jordan. Participants were assigned to three groups: a control group receiving standard care; Intervention Group 1, receiving standard care with weekly text reminders and follow-up calls; and Intervention Group 2, receiving the same components as Intervention Group 1, plus small group education sessions and hands-on foot care training. Generalized Estimating Equations models were used to assess the impact of the interventions on foot care practices and self-efficacy over an 8-week period.ResultsThe findings revealed that participants in Intervention Group 2 demonstrated the most significant improvements in both foot care practices and self-efficacy. For foot care practices, Intervention Group 2 had adjusted odds ratios (aORs) of 2.5 (95% CI: 1.3–5.1) and 1.7 (95% CI: 1.2–2.9) when compared to the control group and Intervention Group 1, respectively. Similarly, for self-efficacy, the aORs for Intervention Group 2 were 2.7 (95% CI: 1.4–5.2) relative to the control group, and 1.8 (95% CI: 1.1–3.2) compared to Intervention Group 1.ConclusionOur study demonstrates that interactive educational approaches—featuring group discussions, real-time problem-solving, immediate feedback, and family support—can empower diabetic women to take a more active role in managing their foot health. Routine clinical care alone is insufficient to promote proactive foot care behaviors, highlighting the need for healthcare providers to incorporate educational materials tailored to the local cultural context into standard care to enhance patient outcomes.